On IT enabling of business process reengineering in organizations - Sungau, Joseph; Msanjila, Simon Samwel (Advanced Materials Research, 2024)
Business Process Reengineering (BPR) is a management approach used to improve organizational performance through restructuring production activities of the core services to enhance their efficiency and effectiveness. Although BPR improves the efficiency of processes, it can hardly be applied in its own and thus it needs to be complemented with other concepts from other disciplines. Information technology (IT) tools are seen as accurate and effective enablers of the BPR approach in restructuring activities. This paper focuses on analyzing how IT can be an enabler of the BPR approach to restructuring processes in an organization to enhance the effectiveness and efficiency of processes. It presents the roles of IT in BPR for organizations. It also presents challenges for organizations when implementing the BPR.